Bioimpedance and bioelectricity basics - Grimnes, Sverre (Academic, 2000)
Bioimpedance and Bioelectricity Basics is unique in providing all the information needed to follow the interdisciplinary subjects of bioimpedance and bioelectricity without having to be a graduate student in the relevant fields. For the first time, one book offers the broadest possible introduction to all use and effects of electrical fields in tissue, dealing with the most basic chemical and physical functions of life. Very few books have covered the dielectric and electrochemical side of the subject, despite its importance; Bioimpedance and Bioelectricity Basics does. It also includes the electrical engineering concepts of network theory and the complex math needed. Up to now, there has been work done by physicists and engineers on one side, doctors and biologists on the other, this book fills the gap, providing the knowledge for both groups. Key Features * is one complete source and reference guide to a complex and disparate field * gives the reader the latest research and applications * is highly illustrated, with an indepth explanation of all mathematics.